Molecular Characteristics of Managing Sclerotinia sclerotiorum Stem Rot in Oilseed Crops - Navin C Gupta; Pankaj Sharma (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Sclerotinia sclerotiorum (Lib.) de Bary is a widely distributed plant pathogenic fungus known for having the broadest host range of any plant pathogen. It affects over 400 species across 275 genera, including important cruciferous vegetables like cabbage and cauliflower, tomato, potato, sunflower, soybean, lettuce, and many other plant species. This pathogen predominantly impacts major oilseed crops like canola (Brassica rapa and B. napus) and Indian mustard (B. juncea). The aggressive nature of Sclerotinia sclerotiorum and the constant evolutionary pressures it faces refine its molecular strategies for successful pathogenesis. As a necrotrophic phytopathogen, it is found globally, affecting a vast number of host species. Control measures such as fungicide applications, cultural practices, and crop rotation are commonly employed by farmers. However, these methods can be expensive, and the uncertainty regarding the appropriate doses and timing for fungicide application poses significant challenges to their routine use. While partial resistance or tolerance has been reported in B. napus and B. carinata, no source of resistance has been identified in B. juncea, which complicates resistance breeding efforts. Recent advancements in biotechnological interventions show promise in developing alternatives to combat Sclerotinia stem rot disease. Techniques such as fungal growth inhibition, activation of defense responses, detoxification of virulence factors, and RNA interference (RNAi) or Host-Induced Gene Silencing (HIGS) can facilitate engineered resistance. Developing transgenic oilseed lines that incorporate natural resistance or innate immunity to S. sclerotiorum through genetic engineering represents a potential alternative to existing practices, addressing growers’ demands for innovative solutions. Furthermore, a deeper understanding of the molecular mechanisms involved in S. sclerotiorum pathogenesis is crucial for its effective application in research and practical solutions.